Distribution, bioaccumulation and trophic transfer of chlorinated polyfluoroalkyl ether sulfonic acids in the marine food web of Bohai, China. (October 2018) - Chen, Hong; Han, Jianbo; Cheng, Jiayi; Sun, Ruijun; Wang, Xiaomeng; Han, Gengchen; Yang, Wenchao; He, Xin
Abstract: Chlorinated polyfluoroalkyl ether sulfonic acids (Cl-PFESAs) caused great concerns recently as novel fluorinated alternatives. However, information on their bioconcentration, bioaccumulation and biomagnification in marine ecosystems is limited. In this study, 152 biological samples including invertebrates, fishes, seabirds and mammals collected from Bohai Sea of China were analyzed to investigate the residual level, spatial distribution, bioaccumulation and biomagnification of Cl-PFESAs. 6:2 Cl-PFESA was found in concentrations ranging from <MDL (method detection limit) to 3.84 ng/g ww and it is the dominant congener when compared with concentrations of 8:2 Cl-PFESA. Compared with other bays and regions, levels of 6:2 Cl-PFESA are relatively high in bivalves and fishes from Liaodong Bay. These levels were also found to tend to increase as compared with those in 2010–2014. Logarithm bioaccumulation factors (BAFs) for 6:2 Cl-PFESA ranged from 2.23 to 4.21, implying the bioaccumulation of this compound. The trophic magnification factor (BMF) for 6:2 Cl-PFESA was determined to be 3.37 in the marine food web, indicating biomagnification potential along the marine food chain. Graphical abstract: Highlights: Concentrations of Cl-PFESAs in 152 marine organism samples from the Bohai Sea of China were investigated. Log BAFs for 6:2 Cl-PFESA ranged from 2.23 to 4.21, implying the bioaccumulation of this compound. The trophic magnification factor (BMF) for 6:2 Cl-PFESA was determined to be 3.37 in the marine food web. Abstract : Levels, spatial distribution, bioaccumulation and biomagnification of chlorinated polyfluoroalkyl ether sulfonic acids (Cl-PFESAs) in Bohai Sea, China were systematically investigated.